Aspectos psicológicos de la toxicidad de la quimioterapia - Rivera, Fernando; López, Carlos; López, Ana; Vega, Mª Eugenia; García, Almudena; Juan, Ana de; López, José Manuel; Ramos, Javier (Psicooncología, 2004)
Oncological treatment of cancer patients still requires in the majority of cases chemotherapy and/or radiotherapy. Due to their lack of specificity, they are aggressive treatments that can cause different toxicities. Nowadays, new more selective and, therefore, less aggressive treatments against healthy tissues are being developped. Meanwhile, it is essential to inform patients against the expected toxicity of each drug, to inform them about toxicity prevention and about the treatment required on each case. Moreover, it is very important to prepare them psychologically, to relieve them and to prepare them to face the treatment in the best possible way. In order to achieve so, it is extremely valuable to know that paradoxically the more common or potentially lethal toxicities from the doctor’s point of view might not match in some cases with those that distress the patient. Therefore, if this information is not taken into account in advance, all the help that might be given could result in fact worthless. The aim is to minimize cancer and chemotherapy consequences improving quality of life.